Technology forecasting for flexible manufacturing system in pharmaceutical manufacturing - Cairo, Ricardo S.; Imbang, Glen (Quezon City University of the Philippines Diliman, 2009)
Introduction. Company Background : GlaxoSmithKline Philippines. GSK is the no. 1 MNC pharmaceutical and healthcare company in the Philippines with 11 percent market share and Php8.3 Billion annual turnover. The Company stands on three strong pillars namely, the pharmaceuticals, consumer healthcare and vaccines. It is the market leader in the areas of anti-infective, respiratory and vaccines. Consumer healthcare adds breadth to GSK's product offering. GSK is the 4th leading company in this sector. GSK Philippines has its own manufacturing facility located at Don Celso Tuason Avenue, Cainta, Rizal to supply both pharmaceutical and majority of consumer healthcare products for domestic. It is the largest MNC manufacturing facility in the country. The Cainta Plant manufactures 4 types of dosage forms-tablets, semisolids, capsules and liquids, which can support both pharma and consumer lines. The tablet and capsule product lines can accommodate to produce 2-3 products at a time. The semisolids line can only produce 1 product at a time while the liquids line can produce 4 products at a time and with one automated line. It does not have the capability to produce antibiotics, vitamins, vaccines and sterile drug products. These products are either imported from other GSK sites or toll manufactured by Third Party Contractors. Mission. "GSK's global quest is to improve the quality of human life by enabling people to do more, feel better and live longer." GSK will dedicate itself to delivering innovative medicines and products that help millions of people around the world live longer, healthier and happier lives. For GSK, this should be "quest"- a daily search for ways that GSK, as individuals, can contribute its time, its talents and its ideas to achieve as a company what is a truly noble mission for the benefit of society. Our Spirit "GSK undertake its quest with the enthusiasm of entrepreneurs, excited by the constant search for innovation. It value performance achieved with integrity. It will attain success as a world class global leader with each and every one of its people contributing with passion and an unmatched sense of urgency". GSK mission gives them purpose. Its size gives them opportunity. Its spirit gives them the qualities as individuals and as an organization that will enable them to turn its opportunities into achievements. Its spirit will guide them, keep them focused, and differentiate them form the competition. Who are they? They are a global team of creative people, intent on always looking for new and better ways to do their jobs. They will cross borders and boundaries, share with, and learn from one another. They will focus on performance, but recognize there is no achievement without integrity. Products. Prescription medicines. GSK pharmaceutical products include treatments for asthma, bacterial infection, depression, migraine, diabetes, heart failure and digestive conditions. Vaccines. It also market vaccines to protect against illnesses such as influenza, rotavirus, hepatitis A and B, diphtheria, tetanus, typhoid, chicken pox and meningoccimia. Consumer health. GSK bring dental health products and over-the-counter medicines to millions of Filipinos and among these are Astring O Sol, Sensodyne, Aquafresh, Calpol and Dequadin. Current Competitiveness. Global Manufacturing Sites (GMS), where GSK-GMS Philippines (Cainta) falls under, is passionately driven by three forces to maintain its sustainability. These three forces include Operational Excellence (OE), Quality and Compliance. With these three forces in play, GMS' competitive strategy is intensified. The company has a very strict Quality Management System to ensure superior quality products are supplied to the market. It is in this policy that in the Philippines, GSK is the only multi-national pharmaceutical company to keep its own production facility. The facility is also implementing Lean Sigma practices through its Operational Excellence program to eliminate variation and waste in production processes to achieve manufacturing excellence. Situational Analysis : The Philippine Pharmaceutical Industry. The Philippine pharmaceutical industry depends heavily on imports for both raw materials and finished products. Of the 170 million dollars of pharmaceutical imports brought into the country in 1992, less than 2 percent (by volume) were raw materials. The leading national suppliers of pharmaceuticals to the Philippines, in order of sales, are Germany, Switzerland, the United States, Australia and United Kingdom. The Philippine Bureau of Food and Drugs (BFAD) require the registration of imported pharmaceutical and diagnostic products. The registration process is long and tedious, taking from 12-18 months to finish. Philippine drug prices are amongst the highest in Asia. With the generic market representing a negligible part of the market, drug prices remain high, especially considering the majority of the population live below in the low-income category. The issue regarding generic drugs and parallel importation of drugs has been brewing for a long time in the Philippines due to the concern over the high costs of drugs in the country. The Generics Act of 1988 aimed at promoting the production, dissemination, prescription and use of generic drugs was passed allowing trade of generic drugs after the patents on the same have expired. The measure of allowing competition from generic drugs however appeared not to be sufficient, as in 1999 the Philippine Senate Committee on Health asserted that the prices of pharmaceuticals sold in the Philippines are higher than in other Asian countries and the multinational drug companies were asked to look into their pricing structures.
The other approach taken by the government of the Philippines was to use parallel imports of branded drugs from countries where the branded drugs were sold cheaper than in the Philippines. The idea behind this program was to influence multinational drug manufacturers to lower the costs of drugs sold in the Philippines. Under the Administrative Order 85 (series 2000) issued by the Department of Health, the import of generic pharmaceuticals from countries such as India are now allowed in the Philippines. As a result from 2002 to 2004 the Philippines International Trading Corporation (PITC) succeeded in importing low-costs drugs from India and they are now planning to import lower-cost patented drugs from China. Scientific advances enabling companies to develop new drugs for previously untreated conditions. In addition, blockbuster drugs that can represent 50 to 60 percent of pharmaceutical sales are coming off patent within the next few years. With the expiration of more than 50 patents by 2010, pharmaceutical companies are under intense pressure to replace these drugs with new ones. Both of these trends are creating a need for increased investment in research and development to keep the new drug pipelines flowing. The cost of R&D, however, is soaring-- almost doubling in the past five years. It is estimated, for example, that the cost of bringing a new drug to market today is more than US800 million dollars. "Do more, feel better, live longer..." is the global vision of the global GlaxoSmithKline. The goal of the Philippine Site is to become the Center of Excellence in the manufacture of high quality consumer healthcare products in the local and regional market and to support the firm in maintaining its one of the top position in the global pharmaceutical market. This can be translated to something the Site envisioned : The Factory of the Future. The future state of GSK Cainta is to become a very efficient manufacturing facility of liquid-dose products and has the capability of developing new products. This will allow free flowing supply of high quality products to all customers and surely support the company's commercial ambition. Existing volumes produced by the plant can only be marketed locally and issues to supply have been hitting the performance of the plant. The plant faces difficulty in producing high demand products. Twenty percent of the total market sales of GSK Philippines are attributed only to local manufacturing while the 80 percent are from imported goods. Lessening this gap means to increase the manufacturing capability of the plant through product line expansion/plant upgrade, product and process technology transfer and a local R&D setup that will support both technology transfer and the creation of new products. In summary, the challenges of GSK Cainta focus on the following : the capability for rapid new product information in a highly innovative and competitive business which has far shorter time frames than pharmaceuticals. New technologies that will become a fundamental platform for lowering costs and providing flexibility in operations. This challenge can be addressed by implementing strategy that will allow its manufacturing facility to react in less time than normal to introduce new products or customise packaging for a specific market need. A manufacturing technology called flexible/agile manufacturing can be used. Agile manufacturing application possibly could allow GSK to create its processes, tools and training to enable to respond quickly to customer needs and market changes while still controlling costs and quality. This could be achieved by the following key initiatives : First is by upgrading the production facility in Cainta and transform it into an agile manufacturing facility and compliment this capability by rationalizing current product portfolio to eliminate complexities and eventually standardize product sku's (stock keeping units). Flexible Manufacturing System (FMS). In the middle of the 1960s, market competition became more intense. During 1960 to 1970 cost was the primary concern. Later quality became a priority. As the market became more and more complex, speed of delivery became something customer also needed. A new strategy was formulated : Customizability. The companies have to adapt to the environment in which they operate, to be more flexible in their operations and to satisfy different market segments (customizability). Thus the innovation of FMS became related to the effort of gaining competitive advantage. First of all, FMS is a manufacturing technology. Secondly, FMS is a philosophy. "System" is the key word. Philosophically, FMS incorporates a system view of manufacturing. The buzz word for today's manufacturer is "agility". An agile manufacturer is one who is the fastest to the market, operates with the lowest total cost and has the greatest ability to "delight" its customers. FMS is simply one way that manufacturers are able to achieve this agility. An MIT study on competitiveness pointed out that American companies spent twice as much on product innovation as they did on process innovation. Germans and Japanese did just the opposite. In implementing FMS, we need to keep in mind what Peter Drucker (1970) said : "We must become managers of technology not merely users of technology". Since FMS is a technology, well adjusted to the environmental needs, we have to manage it accordingly to fully deliver its purpose and maximize benefits to the industry and society.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Technological forecasting; Pharmaceutical industry; Technology forecasting; Pharmaceutical manufacturing; Manufacturing system